2020
DOI: 10.1038/s41598-020-67748-2
|View full text |Cite
|
Sign up to set email alerts
|

Novel thymoquinone lipidic core nanocapsules with anisamide-polymethacrylate shell for colon cancer cells overexpressing sigma receptors

Abstract: the biggest challenge in colorectal cancer therapy is to avoid intestinal drug absorption before reaching the colon, while focusing on tumor specific delivery with high local concentration and minimal toxicity. in our work, thymoquinone (tQ)-loaded polymeric nanocapsules were prepared using the nanoprecipitation technique using Eudragit S100 as polymeric shell. Conjugation of anisamide as a targeting ligand for sigma receptors overexpressed by colon cancer cells to Eudragit S100 was carried out via carbodiimid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(19 citation statements)
references
References 83 publications
(75 reference statements)
1
18
0
Order By: Relevance
“…On the other hand, Fakhoury et al reported that TQ NPs exhibited equal or more potent anticancer activity compared to free TQ depending on the cancer model [ 18 ]. Moreover, a recent study by Ramzy et al described TQ-encapsulated polymeric NPs targeted to colon cancer cells where the NPs were significantly less potent than free TQ due to sustained drug release [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, Fakhoury et al reported that TQ NPs exhibited equal or more potent anticancer activity compared to free TQ depending on the cancer model [ 18 ]. Moreover, a recent study by Ramzy et al described TQ-encapsulated polymeric NPs targeted to colon cancer cells where the NPs were significantly less potent than free TQ due to sustained drug release [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…The weaker band noted at a higher wave number about 3040 cm −1 was allocated to the stretching noted at the vinylic CïŁżH in the CïŁŸCïŁżH groups. The strong intense peak was observed for Ca‐alg/PVA blends which may due to the presence of strong hydrogen bond interaction with in the alginate chains in the matrix 43 . The XRD patterns of TQ, Ca‐alg/PVA blend and TQ loaded Ca‐alg/PVA blend was shown, the strong intense peak was observed for Ca‐alg/PVA blends which may due to the presence of strong hydrogen bond interaction with in the alginate chains in the matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Other simple molecules used to perform NPs active uptake are anisamide (AA) and phenylboronic acid (PBA) able to bind sigma receptors and sialic acid (SA), respectively. These molecules were successfully investigated by and Ramzy et al (2020). Ramzy et al, functionalized the surface polymeric NPs loaded with thymoquinone (TQ) by using AA, in order to enhance uptake and drug accumulation in colon cancer cells.…”
Section: Active Uptakementioning
confidence: 99%